Roles of nuclear receptors in hepatic stellate cells. (3rd August 2021) - Pu, Shiyun; Zhou, Hongjing; Liu, Yan; Liu, Jiao; Guo, Yuanxin; Zhou, Houfeng
ABSTRACT: Introduction : Hepatic stellate cells (HSCs) are essential for physiological homeostasis of the liver extracellular matrix (ECM). Excessive transdifferentiation of HSC from a quiescent to an activated phenotype contributes to disrupt this balance and can lead to liver fibrosis. Accumulating evidence has suggested that nuclear receptors (NRs) are involved in the regulation of HSC activation, proliferation, and function. Therefore, these NRs may be therapeutic targets to balance ECM homeostasis and inhibit HSC activation in liver fibrosis. Areas covered : In this review, the authors summarized the recent progress in the understanding of the regulatory role of NRs in HSCs and their potential as drug targets in liver fibrosis. Expert opinion : NRs are still potential therapy targets for inhibiting HSCs activation and liver fibrosis. However, the development of NRs agonists or antagonists to inhibit HSCs requires fully consideration of systemic effects.